Innate Lymphoid Cells: A Link between the Nervous System and Microbiota in Intestinal Networks. (20th January 2019) - Han, Lin; Wang, Xin-miao; Di, Sha; Gao, Ze-zheng; Li, Qing-wei; Wu, Hao-ran; Wang, Qing; Zhao, Lin-hua; Tong, Xiao-lin
Abstract : Innate lymphoid cells (ILCs) are a novel family of innate immune cells that act as key coordinators of intestinal mucosal surface immune defense and are essential for maintaining intestinal homeostasis and barrier integrity by responding to locally produced effector cytokines or direct recognition of exogenous or endogenous danger patterns. ILCs are also involved in the pathogenesis of inflammatory bowel disease (IBD). Many studies have demonstrated the occurrence of crosstalk between ILCs and intestinal microbiota, and ILCs have recently been shown to be connected to the enteric nervous system (ENS). Thus, ILCs may act as a key link between the nervous system and microbiota in intestinal networks. In this review, we briefly summarize the role of the ILCs in the intestinal tract (particularly in the context of IBD) and discuss the relationship between ILCs and the microbiota/ENS.